2016
DOI: 10.1111/pan.12933
|View full text |Cite|
|
Sign up to set email alerts
|

Could acupuncture be an adequate alternative to dexamethasone in pediatric tonsillectomy?

Abstract: Acupuncture at P6 bilaterally and CV13 provided similar antiemetic effect to dexamethasone in children undergoing tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Similarly, Moeen compared the antiemetic effects of acupuncture at PC6 and CV13 (located 1 thumb breadth above the midpoint between the umbilicus and the xiphisternum) to dexamethasone in pediatric patients after tonsillectomy. 18 A total of 120 children, 2-8 years old, were enrolled in the randomized, double-blind study. At the start of anesthesia, the control group received intravenous (IV) dexamethasone and sham acupuncture, while the experimental group received acupuncture and IV saline.…”
Section: Results Acupuncturementioning
confidence: 99%
“…Similarly, Moeen compared the antiemetic effects of acupuncture at PC6 and CV13 (located 1 thumb breadth above the midpoint between the umbilicus and the xiphisternum) to dexamethasone in pediatric patients after tonsillectomy. 18 A total of 120 children, 2-8 years old, were enrolled in the randomized, double-blind study. At the start of anesthesia, the control group received intravenous (IV) dexamethasone and sham acupuncture, while the experimental group received acupuncture and IV saline.…”
Section: Results Acupuncturementioning
confidence: 99%
“…Sir –With great interest, we read the article by Seham M. Moeen, entitled “Could acupuncture be an adequate alternative to dexamethasone in pediatric tonsillectomy? ” . The author demonstrated that acupuncture performed at P6 (Nei Guan) bilaterally and CV13 (Shang Wen) may provide antiemetic effects similar to prophylactic dexamethasone in children undergoing tonsillectomy.…”
mentioning
confidence: 99%
“…S ir —We thank Dr Cox for his interest in our research about acupuncture and postoperative vomiting in children undergoing tonsillectomy and for his relevant and valuable comments . In our method section, we had defined both dexamethasone and acupuncture groups; a Cun, “the unit of traditional Chinese medicine measurement”; acupuncture needles; and then the acupuncture needling technique of both groups (All needles were kept in place for 20 min and manually stimulated for 5 s [by needle rotation through 180°] every 5 min and just before needle removal) . Indeed, acupuncture technique was started immediately after induction of anesthesia and maintained for about 7–8 min before start of surgery and then for 12–13 min after start of surgery (period during which positioning and sterilization of children occur), so we think that it did not disturbed the surgery.…”
mentioning
confidence: 99%
“…We reported that subjects receiving dexamethasone have statistically significant but clinically insignificant less pain than those receiving acupuncture at 12 and 18 h postoperatively , as the clinically significant pain difference between both groups was defined as >2/15 for PPMP .…”
mentioning
confidence: 99%